Correlative Study between Personality Traits, Student Mental Skills and Educational Outcomes - Oussama Bouiri; Said Lotfi; Mohammed Talbi (MDPI AG, 2021)
The main purpose of this study is determining the correlations between personality traits, academic mental skills and educational outcomes using a quantitative methodology, based on a non-experimental, correlational study. In addition, the following variables are taken into consideration: gender, grade averages and school cycle. The sample is composed of 695 students: these are two institutions (middle and high school) under the provincial direction of Mediouna. In order to gather the information, participants were asked to complete the 16pf 5 questionnaire and scale measuring academic mental skills. Note that the results obtained are processed by the IBM SPSS 23 software. The results demonstrate that the 16 personality scales of the Cattell 16PF5 test and the 9 school grades have significant correlations: 77.77% of all correlations, with essentially the following factors: abstractedness, tension, emotional stability, dominance, social-boldness, vigilance and apprehension maintain (8/9) significant and positive relationships with 38.88% and low intensity (r = 0.031 to 0.0465). Additionally, mental skills (affective, cognitive and metacognitive strategies) and grades have significant correlations with 70.37% of all calculated correlations, with low, average and/or positive, negative intensities, according to each strategy with each grade of school subjects. In the end, it is necessary to make considerable efforts to better understanding the multidimensionality of school success and to ensure an effective and relevant pedagogical intervention.